2023
DOI: 10.1136/bmjgh-2022-011071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of community health worker home visits on antenatal care and institutional delivery: an analysis of secondary outcomes from a cluster randomised trial in Mali

Abstract: IntroductionThough community health workers (CHWs) have improved access to antenatal care (ANC) and institutional delivery in different settings, it is unclear what package and delivery strategy maximises impact.MethodsThis study reports a secondary aim of the Proactive Community Case Management cluster randomised trial, conducted between December 2016 and April 2020 in Mali. It evaluated whether proactive home visits can improve ANC access at a population level compared with passive site-based care. 137 uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…For maternal health care, our analysis of other secondary trial endpoints (reported elsewhere) [ 35 ] found that proactive CHW home visits increased the likelihood of first trimester antenatal care (ANC) by 11% (risk ratio (RR) = 1.11; 95% CI = 1.02, 1.19) and of four or more ANC visits by 25% (RR = 1.25; 95% CI = 1.08, 1.43), but had no effect on institutional delivery (RR=1.06; 95% CI = 0.91, 1.20). Across trial arms relative to baseline, any ANC attendance increased by 83% (RR = 1.83; 95% CI = 1.78, 1.86), first trimester ANC by 15% (RR = 1.15; 95% CI = 1.06, 1.25), four or more ANC visits by 2.6 times (RR = 2.59; 95% CI = 2.28, 2.91), and institutional delivery by 54% (RR = 1.54; 95% CI = 1.41, 1.66) [ 35 ]. These maternal care results are consistent with the child health care utilisation results insomuch that the bulk of the improvements occurred across both arms, with the proactive service delivery intervention yielding modest incremental benefits, which are nonetheless important for achieving timely, universal health coverage.…”
Section: Discussionmentioning
confidence: 99%
“…For maternal health care, our analysis of other secondary trial endpoints (reported elsewhere) [ 35 ] found that proactive CHW home visits increased the likelihood of first trimester antenatal care (ANC) by 11% (risk ratio (RR) = 1.11; 95% CI = 1.02, 1.19) and of four or more ANC visits by 25% (RR = 1.25; 95% CI = 1.08, 1.43), but had no effect on institutional delivery (RR=1.06; 95% CI = 0.91, 1.20). Across trial arms relative to baseline, any ANC attendance increased by 83% (RR = 1.83; 95% CI = 1.78, 1.86), first trimester ANC by 15% (RR = 1.15; 95% CI = 1.06, 1.25), four or more ANC visits by 2.6 times (RR = 2.59; 95% CI = 2.28, 2.91), and institutional delivery by 54% (RR = 1.54; 95% CI = 1.41, 1.66) [ 35 ]. These maternal care results are consistent with the child health care utilisation results insomuch that the bulk of the improvements occurred across both arms, with the proactive service delivery intervention yielding modest incremental benefits, which are nonetheless important for achieving timely, universal health coverage.…”
Section: Discussionmentioning
confidence: 99%
“…The CHW-driven intervention is being used extensively across the globe for varying health services, from addressing post-partum depression [13], for support in diabetes for immigrants [14], care for childhood diseases in Liberia [15], increasing healthcare access in marginalized communities of New York [16], improve access to cancer care [17], increasing antenatal contacts and promoting institutional deliveries [18], and addressing unmet needs among children with asthma [19]. The CHW-driven intervention is cost-effective and can benefit the unreached population of healthcare [20].…”
Section: Intervention By the Chwsmentioning
confidence: 99%